2013
DOI: 10.7897/2230-8407.04522
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of Mechanism of Action of Rhizophora Mucronata Poir. Bark Extract for Its Antidiabetic Activity by Gut Perfusion and Six Segment Method in Long Evans Rats

Abstract: The aqueous bark extract of Rhizophora mucronata Poir. is used in Bangladesh as a hypoglycemic aid without any knowledge about its probable mode of action . It is an effort to assess the claimed hypoglycemic property of the crude drug and to get some knowledge about it. The Hypoglycemic effects were investigated in the ethanol extract of bark of Rhizophora mucronata Poir on Long Evans rats. Gut perfusion and six segments studies were carried out to assess these activities. In gut-perfusion study the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Gaffar et al (2011) investigated the antidiabetic effect of R. mucronata, which is due to its capacity to inhibit carbohydrate digestion and absorption. Haque et al (2013) reported that the aqueous bark extracts of R. mucronata possess significant hypoglycaemic and antihyperglycaemic activities. The bark extracts of this plant showed dose-dependent antidiabetic effects, which significantly suppressed postprandial hyperglycaemia.…”
Section: Rhizophora Spmentioning
confidence: 99%
“…Gaffar et al (2011) investigated the antidiabetic effect of R. mucronata, which is due to its capacity to inhibit carbohydrate digestion and absorption. Haque et al (2013) reported that the aqueous bark extracts of R. mucronata possess significant hypoglycaemic and antihyperglycaemic activities. The bark extracts of this plant showed dose-dependent antidiabetic effects, which significantly suppressed postprandial hyperglycaemia.…”
Section: Rhizophora Spmentioning
confidence: 99%
“…Pandey., et al [65] have also reported about the hypoglycemic effects of leaves of R. mucronata in the management of diabetes. In a similar study Haque., et al [66] observed a considerable decrease of postprandial hyperglycemia following sugar intake by this plant's bark.…”
Section: Avicennia Marinamentioning
confidence: 92%
“…It was correlated to the presence of insulin-like protein in the extracts [28]. Antidiabetic activity of the aqueous bark extracts of R. mucronata was reported, and the proposed pathway was the glucose absorption inhibition [29].…”
Section: Antidiabetic Activity Using α-Amylase Inhibition Assaymentioning
confidence: 95%